Tripeptides derived from reactive centre loop of potato type II protease inhibitors preferentially inhibit midgut proteases of Helicoverpa armigera - Saikhedkar, Nidhi S.; Joshi, Rakesh S.; Bhoite, Ashwini S.; Mohandasan, Radhika; Yadav, Amit Kumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2018)
Potato type II protease inhibitors (Pin-II PIs) impede the growth of lepidopteran insects by inhibiting serine protease-like enzymes in the larval gut. The three amino acid reactive centre loop (RCL) of these proteinaceous inhibitors is crucial for protease binding and is conserved across the Pin-II family. However, the molecular mechanism and inhibitory potential of the RCL tripeptides in isolation of the native protein has remained elusive. In this study, six peptides corresponding to the RCLs of the predominant Pin-II PIs were identified, synthesized and evaluated for in vitro and in vivo inhibitory activity against serine proteases of the polyphagous insect, Helicoverpa armigera. RCL peptides with sequences PRN, PRY and TRE were found to be potent inhibitors that adversely affected the growth and development of H. armigera. The binding mechanism and differential affinity of the RCL peptides with serine proteases was delineated by crystal structures of complexes of the RCL peptides with trypsin. Residues P1 and P2 of the inhibitors play a crucial role in the interaction and specificity of these inhibitors. Important features of RCL peptides like higher inhibition of insect proteases, enhanced efficacy at alkaline gut pH, longer retention and high stability in insect gut make them suitable molecules for the development of sustainable pest management strategies for crop protection.
Keywords: Helicoverpa armigera; Protease; protease inhibitor; Reactive centre loop peptides

Trehalose transporter-like gene diversity and dynamics enhances stress response and recovery in Helicoverpa armigera - Tellis, Meenakshi B.; Chaudhari, Bhagyashri Y.; Deshpande, Shweta V.; Nikam, Sanika V.; Barvkar, Vitthal T.; Kotkar, Hemlata M.; Joshi, Rakesh S. (Gene, 2023)
Trehalose is a primary sugar and its distribution across the insect body, regulated by trehalose transporters (TRETs), is essential for sugar metabolism and energy homeostasis. The large diversity of Tret-like sugar trans-porters (ST), belonging to SLC2A transporter family, in polyphagous insects probably contributes to their extremely adaptive nature. We aim to study spatio-temporal expression dynamics and functional relevance of ST transcript variants in the lepidopteran model organism, Helicoverpa armigera. Identification of 69 putative Tret-like HaST transcript variants from databases and their digital gene expression analysis indicated tissue and development-specific expression patterns. Phylogenetic and sequence similarity network analysis of HaSTs signify evolutionary divergence, while motif and structure analysis depicted conserved signatures. In vitro gene expression validation for selected genes depicts that HaST09 and 69 are fat body and haemolymph-specific. While, HaST06, 30, 36 and 57 are developmental stage or sex-specific. HaST69 has high expression in the haemolymph of fifth instar larvae. In the presence of trehalose metabolism inhibitors and abiotic stress, HaSTs expression show dysregulation, indicating their possible association with trehalose metabolism and stress re-covery. In vivo gene silencing of HaST69 resulted in reduced trehalose accumulation in the insect body, sug-gesting its plausible role in sugar metabolism. The overall understanding of HaST diversity and expression dynamics highlights their putative roles in sugar transport during adaptation and stress recovery of insects.
Keywords: Gene expression; Helicoverpa armigera; Stress; Transporter-like; trehalose

Tyramine-mediated hyperactivity modulates the dietary habits in Helicoverpa armigera - Patil, Yogita P.; Gawari, Shyam K.; Barvkar, Vitthal T.; Joshi, Rakesh S. (JOURNAL OF CHEMICAL ECOLOGY, 2024)
Keywords: amines; Behavior; dopamine; octopamine; RECEPTOR; sensitivity; SULFAKININ